The Characteristics of Organoleptic and pH Value of Beef Se’i Treated by Lime, Kaffir Lime, and Lemon Juice - Gemini E.M Malelak; Mellianty Prasthika Banoet; Yakob R Noach (Journal of Tropical Animal Science and Technology, 2023)
The aim of this study was to determine the organoleptics characteristics and pH of beef se'i which was given lime, kaffir lime and lemon juice. The study used a completely randomized design (CRD) consisting of 4 treatments and 4 replications. The treatments were (TJ= se'i without orange juice, JN= se’i given lime juice, JP= se’i given kaffir lime juice, JL= se’i given lemon juice). The parameters measured were aroma, color, taste, tenderness and pH value. The statistical analysis results showed that the treatment had a significant effect (P<0.05) on taste. Se’i given citrus juices had a better taste compare to cntrol, however kaffir lime or lemon juice gave better taste compared to lime juice. In conclussion, using lime, kaffir lime or lemon juice cold enhance beef se’i taste.